Afterword: finance crime and the big picture: making connections, future directions - Friedrichs, David O. (Crime, law and social change, 2016)
This special issue of Crime, Law & Social Change, which comes out of the RIT International Workshop on Finance, harm and white collar crime, provides a point of departure for considering some dimensions of the intersection of these core concepts and the larger context within which the matters addressed here need to be considered. Some of the contributors to this special issue are criminologists, some are not, but what they address can be linked with significant contemporary developments within the field of criminology. At the same time white-collar crime in the finance sector is situated in relation to other developments in the larger society and political economy. Some references are made to the diverse disciplinary backgrounds and substantive interests of the contributors. The core objective of this "afterword" is to provide useful points of departure for further exploration of the immensely consequential matters addressed in this special issue of Crime, Law & Social Change.